Penanggulangan Penyalagunaan Minuman Beralkohol Dikalangan Remaja - Rettob, Zainudin; Latupeirissa, Julianus Edwin; Salamor, Anna Maria (Faculty of Law Universitas Pattimura, 2025)
Abuse of alcoholic drinks among teenagers is a portrait of life activities that are often found in almost all remote areas in Indonesia. Even though many legal products in the form of statutory regulations have been made by state administrators, it cannot be denied that there are still deviant behaviors that are often encountered in social life, which are the ones that then cause disruption to the interests of society. other communities. The research method used is Empirical Juridical. Empirical legal research uses inductive reasoning techniques and acceptable truth criteria to search for truth and collect primary data. Surrogate facts are used to carry out appropriate truth-testing induction processes. The impact of alcoholic drinks among teenagers in the PP Kur Tual city sub-district has several kinds of impacts, namely it can increase the crime rate, damage public health, cause fights/brawls and can increase liver disease among teenagers. Prevention efforts are carried out by the police/district police. PP Kur Kota Tual in preventing the distribution and consumption of alcoholic beverages is carried out with repressive efforts, preventive efforts and preventive, social efforts.